The Mediating Role of Critical Thinking in the Relationship Between Personality Traits and Creativity with Academic Performance of Students - Sadegh Hamedinasab; Masoumeh Azizi (آموزش مهندسی ایران, 2021)
The purpose of this study was to investigate the mediating role of critical thinking in the relationship between personality traits and creativity with academic performance of students. The research method is applied and correlational. The study population consisted of all undergraduate engineering students of Birjand University who were studying in the academic year 2018-2019. 180 students were selected by relative stratified sampling method. SPSS and AMOS software were used for data analysis. To collect data, three questionnaires were used: California critical thinking skills form (B), standard creativity questionnaire, personality scale, and performance measures. Students’ academic achievement was considered as their average of the previous year in the academic year 2018. Findings showed that personality traits have a direct and significant effect on critical thinking, creativity on critical thinking, personality traits on academic performance, creativity on academic performance, critical thinking, and personality traits. Creativity through indirect thinking has a direct and significant effect on academic performance. The results of the path analysis also showed that the conceptual model of the research was well-suited.